GENDER-SENSITIVE EDUCATION: A STRATEGIC PATHWAY TO ACHIEVING GENDER EQUALITY IN THE EDUCATIONAL SYSTEM - Hasiyatiningsih Hasiyatiningsih; Ahmad Musaddad (International Conference on Humanity Education and Society (ICHES), 2025)
Gender-sensitive education is a key strategy in addressing disparities in access, participation, and representation within education systems. This study positions gender-sensitive education as a systemic approach to challenging structural bias and creating equitable learning environments for all learners, particularly girls and young women. Using a literature review method, the article analyzes national policies and instructional practices that promote gender equality at institutional and cultural levels. Findings indicate that gender-sensitive education contributes significantly to reducing stereotypes, fostering female leadership, and strengthening teacher capacity to support inclusive classrooms. The study highlights the urgency of integrating genderperspectives into curricula, teacher training, and school facilities, and recommends affirmative policies and participatory evaluation as crucial components of equitable educational development.